2021
DOI: 10.3390/cells10123553
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Molecular Dependencies of Mutant EGFR-Driven Non-Small Cell Lung Cancer

Abstract: Epidermal growth factor receptor (EGFR) mutations are the molecular driver of a subset of non-small cell lung cancers (NSCLC); tumors that harbor these mutations are often dependent on sustained oncogene signaling for survival, a concept known as “oncogene addiction”. Inhibiting EGFR with tyrosine kinase inhibitors has improved clinical outcomes for patients; however, successive generations of inhibitors have failed to prevent the eventual emergence of resistance to targeted agents. Although these tumors have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…6). Such expression pattern of ErbB-1 induces higher proliferative capacity, increased vessel density, cellular atypias, high mitotic activity, and distinctive infiltrative phenotype in both types of tissues, and these changes may bring forth their oncogenic potential [57,[60][61][62][63][64][65]. The observed cytoplasmic and nuclear distribution of ErbBs, especially for ErbB-1 and ErbB-3, besides their membranous localization in the eutopic endometrium during endometriosis may trigger pathogenic potential of eutopic endometrium [66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…6). Such expression pattern of ErbB-1 induces higher proliferative capacity, increased vessel density, cellular atypias, high mitotic activity, and distinctive infiltrative phenotype in both types of tissues, and these changes may bring forth their oncogenic potential [57,[60][61][62][63][64][65]. The observed cytoplasmic and nuclear distribution of ErbBs, especially for ErbB-1 and ErbB-3, besides their membranous localization in the eutopic endometrium during endometriosis may trigger pathogenic potential of eutopic endometrium [66][67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that autophagy allows cancer cells to improve their survival at advanced stages or under therapeutic stress [181][182][183], which ultimately results in small-molecule targeted anticancer drug resistance. On the other hand, fibroblast growth factor receptor 1 (FGFR1) is commonly expressed in all types of cancer and is involved in tumor progression and epithelial-to-mesenchymal transition-related drug resistance to EGFR-TKIs [184][185][186][187]. Thinking together, inhibition of both FGFR1 and autophagy might be an effective method to surmount AZD9291 resistance.…”
Section: Nanomedicines To Overcome Targeted Therapy Resistancementioning
confidence: 99%
“…Interestingly. prolonged activation of EGFR enhances the dependence of lung tumor cells on EGFR signaling [ 6 ]. Additionally, several members of the EGFR family are often co-expressed with the RTK c-Met in various human cancers, and c-Met supports the proliferation and survival of non-small cell lung cancer (NSCLC) cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%